The Sopranos - Polan, Dana (Duke University Press, 2009)
"In its original run on HBO, The Sopranos mattered, and it matters still," Dana Polan asserts early in this analysis of the hit show, in which he sets out to clarify the impact and importance of the series in both its cultural and media-industry contexts. A renowned film and TV scholar, Polan combines a close and extended reading of the show itself-and of select episodes and scenes-with broader attention to the social landscape with which it is in dialogue. For Polan, The Sopranos is a work of playful irony that complicates simplistic attempts to grasp its meanings and values. The show seductively beckons the viewer into an amoral universe, hinting at ways to make sense of its ethically complicated situations, only to challenge the viewer's complacent grasp of things.